2017
DOI: 10.1103/physrevc.95.054913
|View full text |Cite
|
Sign up to set email alerts
|

Elliptic flow of light nuclei

Abstract: Using the coalescence model based on nucleons from a blast-wave model with its parameters fitted to the measured proton transverse momentum spectrum and elliptic flow in heavy ion collisions at the Relativistic Heavy Ion Collider, we study the elliptic flows of light nuclei in these collisions. We find that to describe the measured elliptic flows of deuterons (anti-deuterons) and tritons (helium-3) requires that the emission source for nucleons of high transverse momentum is more elongated along the reaction p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 43 publications
2
28
0
Order By: Relevance
“…These previous studies [18,19] have revealed that the formation of light nuclei is very sensitive to the phasespace distributions of protons and neutrons at kinetic freeze-out, which are strongly influenced by the dynamical evolution of the QGP and the hadronic fireball. In the standard model of relativistic heavy ion collisions, the evolving system after thermalization is described by hydrodynamics for the QGP fluid followed by a hadron cascade simulations for the hadronic evolution [25][26][27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…These previous studies [18,19] have revealed that the formation of light nuclei is very sensitive to the phasespace distributions of protons and neutrons at kinetic freeze-out, which are strongly influenced by the dynamical evolution of the QGP and the hadronic fireball. In the standard model of relativistic heavy ion collisions, the evolving system after thermalization is described by hydrodynamics for the QGP fluid followed by a hadron cascade simulations for the hadronic evolution [25][26][27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…In the statistical model, the yields of hadrons and light nuclei can be nicely described with a few parameters related to the chemical freeze-out conditions [10,11]. In the coalescence model, light nuclei are formed through the recombination of protons and neutrons with close positions and velocities on the kinetic freeze-out surface [12][13][14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a simplified picture, the (explosive) expansion is driven by the initial pressure and therefore links the pressure to the finally observable transverse momentum spectra and its anisotropy in the observed hadrons [3][4][5][6]. During the last 20 years the study of flow has been refined and the transverse expansion is now studied in terms of a Fourier decomposition, see [7][8][9][10][11][12][13][14][15][16][17] for an overview of the experimental activities and see [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] for the corresponding theoretical investigations. These flow components, called v n , are the expansion coefficients of the Fourier-series of the transverse momentum distribution [18]:…”
Section: Introductionmentioning
confidence: 99%